Predictive, preventive and personalized project of vascular cognitive impairment in China (P3): Study design and interim baseline patient characteristics of a Nationwide multicenter prospective registry - Linlin Wang; Jiwei Jiang; Yanli Wang; Gaifen Liu; Wenyi Li; Qiwei Ren; Shirui Jiang; Min Zhao; Huiying Zhang; Tianlin Jiang; Shiyi Yang; Mei Cui; et al. (Aging Medicine)
Abstract Objectives To outline the design of the P3 study and serve as a summary of the interim baseline patient characteristics. Methods P3 study is a multicenter, prospective cohort study targeting 1000 acute ischemic stroke (AIS) and cerebral small vessel disease (CSVD) patients with a 2‐year follow‐up from 80 participating hospitals across China. Comprehensive multimodal imaging, neuropsychological tests, and biological samples were collected prospectively on admission and follow‐up visits. Patients were interviewed face to face for 2 years and followed up. Results Until 30 December 2023, 642 patients were enrolled from 67 centers. In the AIS cohort, 219 patients (72.5%) were diagnosed with acute post‐stroke cognitive impairment (PSCI). Compared to those without PSCI, the acute PSCI group exhibited significantly lower levels of education and a history of stroke (all P < 0.05). In the CSVD cohort, 53 patients (41.4%) were diagnosed with cognitive impairment. Compared to those with normal cognitive function, the impaired cognitive function group had a significantly higher prevalence of hypertension and diabetes history (all P < 0.05). All 642 patients completed 20 tests, as well as clinical information and blood sample collection. Nearly 95% of the patients underwent structural MRI and ASL, and 60% of patients completed fMRI and DKI or DTI. Conclusions P3 study aims to establish a comprehensive spatiotemporal profile of VCI. Through multidimensional analysis of clinical information, radiomics, proteomics, metabolomics, microbiomics, and genetics, provide a more comprehensive understanding of VCI trajectories and individual variability, enhancing early detection and prognosis management.